Intensification of lipid-lowering therapy in very high-risk patients: potential of combination with PCSK9 inhibitors - D. Yu. Sedykh; V. V. Kashtalap; O. N. Khryachkova; T. S. Petrova; O. L. Barbarash (Российский кардиологический журнал)
Aim. To assess the efficacy and safety of 6-month combined lipid-lowering therapy with a PCSK9 inhibitor in patients with very high cardiovascular risk (CVR).Material and methods. This prospective, open-label, single-center exploratory research study with active treatment included 5 outpatients with very high CVR. So, 80% of patients had prior coronary artery disease, 20% peripheral arterial disease, and 60% old myocardial infarction. The key inclusion criterion was the failure to achieve the target low-density lipoprotein cholesterol (LDL-C) <1,4 mmol/l with high-intensity statin monotherapy at the maximal tolerated doses or combination therapy with ezetimibe. On a regular basis, all included patients took atorvastatin 40-80 mg/day or rosuvastatin 20-40 mg/day, or pitavastatin 2-4 mg/day. In addition, 2 patients received a statin in combination with ezetimibe 10 mg/day. Patients were followed up for 6 months as follows: every 2 weeks, with a lipid profile monitoring, subcutaneous injections of alirocumab at a dose of 150 mg/ml were performed. Additionally, clinical and laboratory indicators of the safety of therapy were evaluated.Results. After 6 months, with the combined lipid-lowering therapy with alirocumab, a decrease in median LDL-C from 4,3 (4,11-4,67) to 1,27 (1,06-1,47) (p=0,001) mmol/l, total cholesterol from 6,1 (6-7) to 3,7 (3,5-3,9) (p=0,018) mmol/l, atherogenic index from 3,2 (3-3,26) to 0,8% (0,8-1,5) (p=0,001). There was no significant decrease in median triglycerides and an increase in median high-density lipoprotein cholesterol. Six-month lipid-lowering therapy with a PCSK9 inhibitor had no adverse events and made it possible to achieve a maximum decrease in LDL-C by an average of 75,4% already by 4 months of treatment in actual clinical practice.Conclusion. Six-month combined lipid-lowering therapy with alirocumab 150 mg subcutaneously every 2 weeks in very high-risk patients allows the majority of patients to achieve target LDL-C values.